2402. Daptomycin Pulmonary Eosinophilia: Review of Cases and New Hyperacute Syndromic Presentation. (26th November 2018) - West, Katelyn; Mackay, Kimberly; Forrest, Graeme N
Abstract: Background: Daptomycin pulmonary eosinophilia (DPE) has been described as a rare event. Since the Food and Drug Administration (FDA) first described the syndrome which occurs about 3 weeks after starting the drug, it continues to be a miss diagnosed. Most outpatient antibiotic treatment (OPAT) programs focus on screening for CPK elevations. We describe an unusual increase in DPE at our center including acute reactions on re-exposure to daptomycin. Methods: Retrospective review from local VA pharmacy and OPAT database of adverse drug events (ADE) with daptomycin from 2010 to April 2018. Data evaluated include, age, gender, weight, body mass index (BMI), daptomycin dosing, indication for use, duration of therapy, time to symptom onset, Creatinine clearance, white cell count (WCC), %eosinophilia (%eos), admission to intensive care unit (ICU), and clinical outcomes or interventions. Results: There were 363 unique initiations of Daptomycin in the time period. There were 17 DPE (5%) and 3 CPK (0.6%) events in that time period. The medians for all DPE was; Age 68 years (range 55–95), BMI 29 m/kg 2 (range 21–49.5), daptomycin dose 500 mg (>7 mg/kg), baseline CrCl 35.5 mL/minute, eosinophilia at onset of DPE 9% (8–44%), and duration of therapy to onset was 21 days (1–33). All recovered on removal of daptomycin, but 5 patients required adjunctive corticosteroid therapy. Four patients had a severe and novel hyperacute DPE within 48 hours of a new initiation of daptomycin therapy. All 4 patients had prior exposure to daptomycin in the last 12 months. They presented with hypoxic respiratory failure, abnormal chest x-rays and/or CT chest scans, with preceding systemic fevers and fatigue after the first dose. All had low grade %eos (3–5%) on prior use, and all recovered rapidly with discontinuation of daptomycin. Conclusion: DPE may be underreported and is associated with doses of 500 mg or >7 mg/kg, with CrCl <35 mL/minute and older age. Of concern are the new cases of hyperacute DPE within 48 hours of re-exposure to daptomycin that we have seen, who had prior low-grade eosinophilia. Close monitoring of these factors may be warranted in at risk individuals. Disclosures: All authors: No reported disclosures.